2016
DOI: 10.2147/dddt.s94056
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide suppresses thymic stromal lymphopoietin in phorbol myristate acetate/calcium ionophore A23187-activated mast cells and 2,4-dinitrofluorobenzene-induced atopic dermatitis-like mice model

Abstract: BackgroundAtopic dermatitis (AD) is one of the most common inflammatory cutaneous diseases. Thymic stromal lymphopoietin (TSLP) has been demonstrated to be an important immunologic factor in the pathogenesis of AD. The production of TSLP can be induced by a high level of intracellular calcium concentration and activation of the receptor-interacting protein 2/caspase-1/NF-κB pathway. Andrographolide (ANDRO), a natural bicyclic diterpenoid lactone, has been found to exert anti-inflammatory effects in gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Besides, it can also decrease thymic stromal lymphopoietin (TSLP) in skin lesions. Further study showed that andrographolide suppressed the RIP2/Caspase‐1/NF‐κB pathway, thereby blocking TSLP levels in HMC‐1 cell lines 191 …”
Section: Andrographolide In Inflammatory Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, it can also decrease thymic stromal lymphopoietin (TSLP) in skin lesions. Further study showed that andrographolide suppressed the RIP2/Caspase‐1/NF‐κB pathway, thereby blocking TSLP levels in HMC‐1 cell lines 191 …”
Section: Andrographolide In Inflammatory Diseasesmentioning
confidence: 98%
“…Further study showed that andrographolide suppressed the RIP2/Caspase-1/NF-κB pathway, thereby blocking TSLP levels in HMC-1 cell lines. 191 Exposure of skin to ultraviolet (UV) radiation gives rise to skin oxidative stress and inflammation, as well as consequent premature aging. 192 In a UV-induced skin photoaging mouse model, andrographolide was found to resist skin thickness, wrinkles, loss of elasticity, and loss of water content, presumably by reducing oxidative stress and inflammatory responses.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%
“…In a murine model of malaria infection, andrographolide significantly decreased the levels of proinflammatory cytokine IFN-γ and improved the levels of anti-inflammatory cytokines IL-10 and IL-4, and the mechanism may have partly involved the regulation of serine/threonine kinase and GSK3β and inhibition of the NF-κB pathway ( Hassan et al, 2019 ). In mast cells and mice with atopic dermatitis, andrographolide can inhibit the expression of thymic interstitial lymphopoietin by inhibiting Caspase-1/RIP2/NF-κB activity and inhibit the inflammatory response to treat idiopathic dermatitis ( Li et al, 2016 ). In imiquimod-induced mouse psoriasis, andrographolide inhibited the generation of proinflammatory cytokines such as IL-23 and IL-1b and induced the autophagic proteolysis of MyD88, which controlled MyD88-dependent cytokine activation and alleviated psoriasis ( Shao et al, 2016 ).…”
Section: Other Inflammatory Diseasesmentioning
confidence: 99%